Improvement of Boron Doping in SiGe Raised Sources and Drains for FD-SOI Technology by Carbon Incorporation. (18th August 2016) - Labrot, Maxime; Cheynis, Fabien; Barge, David; Juhel, Marc; Müller, Pierre
Abstract : Selective epitaxial growth (SEG) of highly boron-doped SiGe (SiGe:B) is a key step to realize Raised Source and Drain (RSD) for applications in SiGe-based microelectronic devices. This paper is devoted to the optimization of boron dopant profiles in SiGe RSD. For this purpose Fully-Depleted Silicon-On-Insulator (FD-SOI) blanket and patterned wafers are considered. We show that, in both situations, a weak carbon incorporation increases the dopant level and flattens the boron profile in the RSD. Finally experimental conditions for optimal RSD fabrication are reported.